Regional Development Bank Competition: Evidence from Indonesia - Zunairoh, Zunairoh; Wijaya, Liliana Inggrit; Mahadwartha, Putu Anom; Murhadi, Werner Ria (University of Merdeka Malang, 2023)
Regional development banks are intermediary institutions that can develop the national economy and drive regional development through local government management. This study aims to analyze the effect of competition in regional development banks on efficiency with risk as a moderating variable. This study uses the regression panel data estimation technique based on data from regional development banks in Indonesia for the period 2016- 2020, a total of 130 observations. The novelty of this study is that it is still rare to examine using a sample of regional development banks using the Leaner Index model to analyze bank competition. This study finds that competition negatively and significantly affects efficiency at regional development banks in Indonesia. Risk strengthens the impact of competition on efficiency. The unstoppable competition requires banks to make several efficiencies both from the micro and macro sides to survive. Regional development banks are very close to local governments, so they should be able to optimize investments in technology-based products and services and improve credit quality.JEL: G2, G21, G28